Percentage points for testing homogeneity of covariance matrices of several bivariate Gaussian populations (2021)
In this article, the exact distribution and exact percentage points for testing equality of covariance matrices of q bivariate Gaussian populations are obtained. The distribution has been derived using the inverse Mellin transformation and the residue theorem. The percentage points have been computed for q = 2(1)5.